2014
DOI: 10.1088/2053-1591/1/1/015028
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long Fe nanowires by pulsed electrodeposition with full filling of alumina templates

Abstract: With the increasing demand for high quality methods for the fast fabrication of extremely high aspect ratio nanoparticles, the research for efficient, low-cost and simple techniques has become fundamental. A promising approach on the synthesis of these materials is here addressed. Pulsed electrodeposition in porous anodic alumina templates was improved enabling, for the first time, a simple and cost effective fabrication method for vertically aligned nanomaterials with aspect ratios never reported with this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…2,28 If their length is higher than 8 lm, both coercivity and squareness show a more pronounced decrease which can be attributed to enhanced magnetostatic interactions among wires 2,29 and to the averaging of inhomogeneities in morphology or in composition along the length of the nanowires due to the decrease of ions in the electrolyte during the electrodeposition. 28,30,31 Figure 5(b) shows the dependence of coercivity and squareness as function of the nanowire diameters for Ni 70 Cu 30 nanowires with length of 8 lm. The coercivity and squareness of nanowires decrease with their diameter.…”
Section: Resultsmentioning
confidence: 99%
“…2,28 If their length is higher than 8 lm, both coercivity and squareness show a more pronounced decrease which can be attributed to enhanced magnetostatic interactions among wires 2,29 and to the averaging of inhomogeneities in morphology or in composition along the length of the nanowires due to the decrease of ions in the electrolyte during the electrodeposition. 28,30,31 Figure 5(b) shows the dependence of coercivity and squareness as function of the nanowire diameters for Ni 70 Cu 30 nanowires with length of 8 lm. The coercivity and squareness of nanowires decrease with their diameter.…”
Section: Resultsmentioning
confidence: 99%
“…The electroplating techniques in PAO templates, made by the conventional anodization process, have been categorized as the alternating current (ac), the direct current (dc), and the pulsed ac and dc electrodepositions [13,[22][23][24][25]. By controlling the parameters involved in the pulsed electrodeposition technique, such as the voltage, current density, shape of the pulse applied and the off-time between pulses, it is possible to tailor the composition, crystalline structure and magnetic properties [15,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the parameters involved in the pulsed electrodeposition technique, such as the voltage, current density, shape of the pulse applied and the off-time between pulses, it is possible to tailor the composition, crystalline structure and magnetic properties [15,23,26,27]. Due to the presence of alumina barrier layer, it is necessary to remove this insulator before performing the pulsed dc electrodeposition and consequently sputtering an electrical contact at the bottom of nanopores [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Oxalic acid was used due to its high reproducibility rate and because it yields nanometric pore diameter necessary for high surface areas 22 . Other pore sizes are currently under study and not reported in this work.…”
Section: Resultsmentioning
confidence: 99%